Pelatihan Jurnalistik Dasar di UPT SMA Negeri 3 Sinjai - Asriadi; Putri Utami, Adeh Ijam; Akmal (INKAMKU : Journal of Community Service, 2024)
Journalism is the activity of processing news materials, ranging from coverage to the preparation of a decent disseminated to the public. Journalism is defined as the activity of delivering messages to audiences through organized communication media. The purpose of this community service is to improve the quality of self, prepare students in the future to face the next, provide the ability to write news. In the community service conducted, there are implementation methods that are applied, among others, determining the criteria for participants to be invited to the activity, inviting participants, building an understanding of journalism, and providing motivation for journalistic skills to the younger generation. Journalism focuses on collecting news material, reporting events, writing news, editing news scripts, and presenting or disseminating news through the media. Elements in a news is the most important thing in the journalistic process. Elements in the news the most important is 5w+1H. These 5W+1H elements include, what, who, when, where, why, and how. Basic journalism training have a great influence on students in training and developing interests and talents in the world of journalism. Students also benefit from this activity, namely the ability to write news into an alternative profession in the future. With the implementation of this training, participants are expected to improve their knowledge and have the ability to write news.